Kinetics of steam reforming over a Ni/Alumina catalyst - KO, KD; LEE, JK; PARK, D; SHIN, SH (한국화학공학회, 1995)
Steam reforming of methane over a commercially available, nickel/alumina catalyst was experimentally studied. The reactor employed for the study was made of 7 mm i.d. quartz tube and catalyst particles were 0.841 mm in size. The amount of catalyst charge in the reader was around 0.3 gram. Experiments were carried out varying the steam to methane ratio in the feed gas from 1 to 10 and reaction temperature from 823 to 1073 K. Nitrogen gas was used to control partial pressure of methane and steam. Using Marquardt method reaction rate derived from the experiments was fitted to reaction rate = 527exp(-14,820/RT) (PCH4PH2O-0.9577)-P-1.014 Thus reaction order was close to one for methane and close to minus one for steam, respectively.